Effect of Vapor-injection Mass on System Performance of Air-source Heat Pump with Enhanced Vapor Injection - Ran Xiaopeng; Zhai Xiaoqiang; Luo Qiong (Zhileng xuebao)
Air-source heat pumps suffer from many problems such as high pressure ratio, high discharge temperature, and poor performance at low temperature. The enhanced vapor injection (EVI) technology can improve the performance of an air-source heat pump at low temperature. This study sets up a numerical simulation model of an air-source heat pump system to investigate with the effect of EVI. A test bed is designed to verify the simulation model. The performance of the air-source heat pump with EVI is simulated based on the model. The results demonstrate that an optimal relative vapor-injection mass exists that achieves the highest system energy efficiency. The best range of relative vapor-injection mass is 8%–10% for the best heating performance when the environment temperature is lower than ?6 ℃. The best range of relative vapor-injection mass is 5%–8% when the environment temperature is from ?6 to 0 ℃. The best range of relative vapor-injection mass is 4%–5% when the environment temperature is higher than 0 ℃. The corresponding optimal relative vapor-injection pressure is between 0.7 and 0.9. The heating capacity increases by 33%, and the coefficient of performance increases by 31% under optimal air-injection parameters.